2019
DOI: 10.1002/jimd.12038
|View full text |Cite
|
Sign up to set email alerts
|

Results from a 78‐week, single‐arm, open‐label phase 2 study to evaluate UX007 in pediatric and adult patients with severe long‐chain fatty acid oxidation disorders (LC‐FAOD)

Abstract: Summary Long-chain fatty acid oxidation disorders (LC-FAOD) are rare disorders characterized by acute crises of energy metabolism and severe energy deficiency that may present with cardiomyopathy, hypoglycemia, and/or rhabdomyolysis, which can lead to frequent hospitalizations and early death. An open-label Phase 2 study evaluated the efficacy of UX007, an investigational odd-carbon medium chain triglyceride, in 29 subjects with severe LC-FAOD. UX007 was administered over 78 weeks at a target dose of 25%–35% t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
47
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 50 publications
(58 citation statements)
references
References 19 publications
10
47
0
1
Order By: Relevance
“…The results of this clinical trial are consistent with findings from previous triheptanoin studies 7,16,21,22 . Results from the previous triheptanoin study CL201 showed a 48.1% reduction in mean annualized total MCE event rate and a 50.3% reduction in mean annualized total MCE event duration (days/year) compared to an 18‐month pre‐triheptanoin period.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The results of this clinical trial are consistent with findings from previous triheptanoin studies 7,16,21,22 . Results from the previous triheptanoin study CL201 showed a 48.1% reduction in mean annualized total MCE event rate and a 50.3% reduction in mean annualized total MCE event duration (days/year) compared to an 18‐month pre‐triheptanoin period.…”
Section: Discussionsupporting
confidence: 89%
“…For MCE event type, mean annualized event rate decreased 32% for rhabdomyolysis (mean [SD] events/year: 1.30 [1.53] pre‐triheptanoin to 0.89 [1.05] with triheptanoin), 96% for hypoglycemia (0.383 [0.98] to 0.014 [0.07]), and 33% for cardiomyopathy (0.083 [0.30] to 0.056 [0.21]). More specifically for hypoglycemia, 12 events occurred in four patients during the pre‐triheptanoin period and only one event occurred during the with‐triheptanoin period on the patient's first day of triheptanoin treatment in CL201 16 . No hypoglycemia events occurred in the CL201 rollover group during CL202.…”
Section: Resultsmentioning
confidence: 98%
“…Despite these measures, morbidity and mortality remain high [ 5 ]. With no approved specific medication for treatment of LC-FAODs available, triheptanoin constitutes a promising agent that is currently used in compassionate care programs [ 6 , 7 ]. Triheptanoin is a highly purified, synthetic seven odd-chain fatty acid triglyceride that can bypass the deficient long-chain oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Further studies performed preferentially in vivo in animal models and in patients affected by FAOD are therefore necessary to further clarify the underlying mechanisms of tissue damage in these disorders. Finally, it is expected that, besides restricting fat dietary intake and avoiding fasting, drugs that stimulate mitochondrial function such as bezafibrate and the anaplerotic compound triheptanoin may hopefully improve the clinical outcome of the affected patients (Gillingham et al, 2017;Vockley et al, 2017Vockley et al, , 2019Yamada et al, 2018;Shiraishi et al, 2019;Suyama et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, the clinical efficacy of bezafibrate is still disputed and needs to be further confirmed (Ørngreen et al, 2014, 2015). Furthermore, replacement of longchain triglycerides by MCT and replenishment of citric acid cycle (CAC) intermediates by the seven-carbon fatty acid triglyceride (C7) triheptanoin to support ATP production have been recently demonstrated to improve the clinical outcome of these patients (Gillingham et al, 2017;Vockley et al, 2017Vockley et al, , 2019.…”
mentioning
confidence: 99%